Алгоритм визначення необхідності в реструктуризації будівельних підприємств - Башинська, О. Ю. (Ways to Improve Construction Efficiency, 2014)
In the article highlighted the essence of restructuring, presented the algorithm for determining the need of reorganization actions and developed a graphical model for diagnostic the need of restructuring in construction enterprises.